The proposition of the concept of Nursing virtual community – a review study - Brandão, Marcos Antônio Gomes; Peixoto, Mauricio Abreu Pinto; Ferraz, Viviane Modesto (Online Brazilian Journal of Nursing, 2007)
The authors of the paper propose a concept to nursing virtual community based in concepts about communities and virtual communities. In this paper, some aspects that have influenced the creation of a concept to nursing virtual community are also presented, especially, the social interaction, collaboration and cooperation in virtual communities concepts. The authors highlight some issues about virtual groups and nursing virtual communities in Brazil, and discuss specific variables that interfere on interaction inside of community, such as, strategies used to establish or maintain relationship in virtual environments, and interactive and communicational processes rules and philosophies on virtual environment internet-based.